GOOGLE TRANSLATE ANALYSIS ERRORS IN ENGLISH-INDONESIA TRANSLATION TEXT: IDIOM CASES - Napitupulu, Maya Farhanna; Kembaren, Farida Repelita Waty; Sambas, Ela Carmelia Mukti (Universitas Negeri Medan, 2023)
This article digs into the special issues of English-Indonesia translation, concentrating on the complex world of idiomatic phrases. Idioms, which are firmly ingrained in cultural nuances and linguistic complexity, provide a substantial challenge for automatic translation systems. The aims of this study is to examine morphological faults in translated texts using English idiom phrases translated by the Google Translate translation system. A qualitative research design with content analysis is used in this study. Discourse analysis is used in this study, and the research subjects are documents that were gathered from websites by researchers. The study employed document analysis as a means of data collecting by the researcher. By comparing the data to earlier studies on translation and morphology and examining mistakes in grasping idiomatic meaning, the researchers examined the data. According to the findings of the study, there are three translation methods. Based on the morphology of the translation machine, there are eight GT translation errors. The study's findings give Google Translate valuable insight into the need for idiom translations to include additional morphological explanations in order to increase precision and to be revisited within the framework of morphological science.Keyword : Google Translate, English “ Indonesian Translation, Morphology, English Idiom